PENENTUAN AKAR PERSAMAAN NON LINIER DENGAN METODE NUMERIK - Wajib Pandia; Israil Sitepu (Fakultas Ilmu Pendidikan Universitas Sari Mutiara Indonesia, 2021)
Numerical methods are able to solve large, non-linear and very complex equations that cannot be solved analytically. But the numerical method, can only obtain solutions that approach or approach the true solution so that the solution from the results of numerical calculations is called the approximation solution and can be made as precisely as desired. This research type of library research or literature that aims to collect data and information through books and journals. Non-linear equation is one of the problems that can be solved by numerical methods. In determining the roots of non-linear equations there are four methods that can be used, namely the bisection method, false position method, Newton Raphson method, and the secant method, the fastest converging method is the Newton Raphson method.